Restatement of the I-O coefficient stability problem - Emilian Dobrescu (Journal of Economic Structures, 2013)
The capacity of input-output tables to reflect the structural peculiarities of an economy and to forecast, on this basis, its evolution, depends essentially on the characteristics of the matrix A matrix of I-O (or technical) coefficients. However, the temporal behaviour of these coefficients is yet an open question. In most applications, the stability of matrix A is usually admitted. This is a reasonable assumption only for a short-medium term. In the case of longer intervals, the question is much more complicated. We shall empirically discuss this problem by using Romanian input-output tables. Our statistical option was motivated inter alia by the existence of official annual data for two decades (1989-2013;2009). As an introduction, Sect. 1 characterises the general framework of paper. Section 2: The main characteristics of I-O coefficients as statistical time series examines the variability of technical coefficients expressed in both volume and value terms. The analysis is convergent to other previous works, confirming that the evolution of these coefficients in real and nominal terms is roughly similar. The main finding of this section is that, on one hand, the I-O coefficients are volatile, but on the other, they are serially correlated. Consequently, Sect. 3-Attractor hypothesis examines a possible presence of attractors in corresponding statistical series. The paper describes a methodology to approximate these using new indicators obtained by summation in columns and rows of the technical coefficients (colsums scaj and rowsums srai). The RAS method is involved as a connecting technique between these indicators and sectoral data. Section 4: Conclusions presents the main conclusions of the research and outlines several possible future developments. The database and econometric analysis are presented in Statistical and Econometric Appendix.
Keywords: C12; C32; C43; C67; 330; I-O coefficients; volatility; serial correlation; attractor; RAS technique; Input-Output-Analyse; Volatilität; Korrelation; Modellierung; Theorie